Cervical stump carcinoma - Galdós, Ricardo (2015)
The authors have studied 68 cases of carcinoma of the cervical stump treated at the INSTITUTO NACIONAL DE ENFERMEDADES NEOPLASICAS, Lima, between 1952 - 1967. By applying the criteria of two years free interval, 49 of these cases were "authentic" and 19 were of the coincident type. These 68 cases represented 0.7 % of the 9.197 cases of carcinoma of the cervix treated in the 15 years period. The overall survival rate for the surgical treated group was 50 % and 47 % for those who received roentgen therapy; however, after analysis of the clinical stages of the cases in both groups the authors suport radiation therapy as the more adequate procedure.